A precise analytical method for fault location in double-circuit transmission lines. (March 2021) - Gil, Milad; Abdoos, Ali Akbar; Sanaye-Pasand, Majid
Highlights: This paper presents a new method for fault locating in double-circuit transmission lines. The faults are precisely located when the disconnected line is grounded at both sides. It is not affected by the fault resistance, source impedance and transposition strategies. It is also robust against noise and CT saturation. Abstract: The mutual coupling impedance between two circuits of double-circuit transmission lines degrades the performance of the fault location module and ground fault unit of distance relays. The distance measuring unit may underreach when both circuits are in operation. Meanwhile, the overreach problem may arise when one of the parallel circuits is disconnected and grounded at both sides. The appearance of the zero sequence mutual coupling impedance between two circuits causes that single line to ground faults would not be accurately determined by the fault locator module and distance measuring units. Thus, in this paper a new analytical method is presented based on the measurement of voltage and current signals at both ends of the line in service. The fault distance is calculated by analysis of the equivalent sequence network during single line to ground fault condition while the switched-off circuit is grounded at both sides. The proposed formulation for fault location is independent of the fault resistance, so that the estimation accuracy dose not decrease for high fault resistances. In order to evaluate the proposed method performance, a 230 kV double-circuit transmission line is simulated in PSCAD/EMTDC environment considering different transposition strategies. The obtained results show that the proposed method is able to locate the fault distance precisely with the maximum error of 1%, while for most of the cases the error is even much lower. Moreover, fault location, source impedance, external noise and CT saturation have ignorable impact on the estimation accuracy.